25x-6=45x+2

Simple and best practice solution for 25x-6=45x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25x-6=45x+2 equation:


Simplifying
25x + -6 = 45x + 2

Reorder the terms:
-6 + 25x = 45x + 2

Reorder the terms:
-6 + 25x = 2 + 45x

Solving
-6 + 25x = 2 + 45x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-45x' to each side of the equation.
-6 + 25x + -45x = 2 + 45x + -45x

Combine like terms: 25x + -45x = -20x
-6 + -20x = 2 + 45x + -45x

Combine like terms: 45x + -45x = 0
-6 + -20x = 2 + 0
-6 + -20x = 2

Add '6' to each side of the equation.
-6 + 6 + -20x = 2 + 6

Combine like terms: -6 + 6 = 0
0 + -20x = 2 + 6
-20x = 2 + 6

Combine like terms: 2 + 6 = 8
-20x = 8

Divide each side by '-20'.
x = -0.4

Simplifying
x = -0.4

See similar equations:

| f(x)=2.2(5)x | | T-65=75 | | x=-7+4(1.5) | | 8y-3=10+5 | | -3(5a-4)=132 | | x=-7+4y(1.5) | | 8m-5n=5m+7 | | 6x+20=4x+13 | | log(y)=9t-4 | | 76=x^3+3*x | | 8x+2=7(x-2)+4 | | 15x-12y=141 | | 8+40n-35=-307 | | 4x+72=3x+36 | | 2P=q+5 | | -7+4y-2y+4=0 | | 10=a(43)(3) | | 16+11h=7+9+11h | | -11+13v-19v=3-8v | | -20+7t=-13+7t+2 | | x^2+7x-5= | | 0.5x+x=4.75 | | 5x+118+3x+126= | | 10k-5=-3+10k-2 | | -1/2k=3/4k-3 | | 5.8=-logarithm(Ka) | | -7+6n=7+6n | | -15-9+13p=-13+14p | | y=kx+5 | | F(x)=15x-8 | | 5(5x-4)+11=-3 | | 7-3m=40 |

Equations solver categories